Livro infantil multiformato em sistema pictográfico: lançando a semente da inclusão pela via literária, em estudo com professores e seus alunos com TEA - LAGO, Mara Rita Araújo (Universidade Federal do Pará, 2024)
Children with autism, for the most part, need specific mediation and adaptations that can contribute to their learning, among them the following stand out: the multiformat children's book, studied in this research. Thus, the following research question was addressed: how is the adapted book an important tool to contribute to communication, as observed by the researcher and the professors? This study aims to describe the interaction between children and the multiformat children's book, based on the observations made explicit by the teachers in the research questionnaire. The methodology employed consists of a qualitative approach, the data collection occurred through documentary and bibliographic research and online and face-to-face questionnaires, carried out in a school, in early childhood education, in the municipality of Castanhal Pará, involving as subjects, teachers and their autistic students. The results of this work showed how multiformat children's books can help teachers in the methodological aspects in relation to storytelling for their students with autism, stimulating them in communication, understanding the plot of the narrative that permeates the story, having a positive scope, contributing to broaden their development and learning.